Evaluation of Associated Structural and Chromosomal Abnormalities in Patients with Fetal Cerebral Ventriculomegaly Detected in Ultrasonographic Imaging - Erkan Cagliyan; Samican Ozmen; Sureyya Saridas Demir; Ceren Aydin; Egehan Bilen; Handan Guleryuz; Elif Yasar; Derya Ercal; Elcin Bora; Tufan Cankaya (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Fetal cerebral ventriculomegaly is defined as enlarged cerebral lateral ventricles. The etiology of fetal cerebral ventriculomegaly is multifactorial. Aneuploidy in ventriculomegaly is detected especially in moderate and severe ventriculomegaly accompanied by structural anomalies. This study aims to evaluate patients with fetal cerebral ventriculomegaly for associated structural and genetic abnormalities and their obstetric and neonatal outcomes.